Functionalization of spiro[fluorene-9, 9′-xanthene] with diketopyrrolopyrrole to generate a promising, three-dimensional non-fullerene acceptor. (18th September 2020) - Hundal, Amanpreet Kaur; Ali, Salman; Jameel, Mohammed; Jones, Lathe; Kaur, Navneet; Evans, Richard A.; Li, Jing-Liang; Langford, Steven J.; Gupta, Akhil
Abstract : A three-dimensional, non-planar, non-fullerene acceptor (SFX1 ) ITO/PEDOT:PSS (38 nm)/active layer (∼75 nm)/Ca (20 nm)/Al (100 nm) PCE (PTB7 : SFX1 1 : 1.2) = 9.42%. Abstract : A spiro[fluorene-9, 9′-xanthene], often described as a "low-cost spiro, " has been functionalized with terminal diketopyrrolopyrrole units to generate a promising, three-dimensional non-fullerene acceptor. The new acceptor, coded as SFX1, was readily synthesized using the Suzuki cross-coupling reaction and was sufficiently soluble in a variety of commonly used, film-processing solvents such as chlorobenzene and o -dichlorobenzene. SFX1 displayed promising optoelectronic properties and the HOMO/LUMO energy levels complementary to the commercially available and commonly used donor polymers P3HT and PTB7. The joining of two high-potential building blocks – the spiro[fluorene-9, 9′-xanthene] and diketopyrrolopyrrole – demonstrates a new strategy where the device performance [D : A 1 : 1.2 = 9.42% (D = PTB7)] validates its use as a potential, three-dimensional non-fullerene acceptor.